Hueter-Volkmann Law; How It Influences the Correction of Scoliosis Curves with Braces? - Mohammad Karimi (Journal of Orthopedic and Spine Trauma)
According to the Hueter-Volkmann law, there is asymmetry in the loads applied to the spinal structure on the convex and concave sides, which can increase the severity of scoliosis and its progression. The purpose of this review was to examine the asymmetry of vertebrae in subjects with scoliosis and explore how this theory can be utilized to enhance the effectiveness of braces in controlling and reducing scoliosis curves. A search was conducted in databases such as Google Scholar, PubMed, and ISI Web of Knowledge using keywords like Hueter-Volkmann law and asymmetry in relation to scoliosis.